2014
DOI: 10.1007/s10903-014-0108-6
|View full text |Cite
|
Sign up to set email alerts
|

Do First Generation Immigrant Adolescents Face Higher Rates of Bullying, Violence and Suicidal Behaviours Than Do Third Generation and Native Born?

Abstract: We conducted a systematic review to examine first generation immigrant adolescents’ likelihood of experiencing bullying, violence, and suicidal behaviours compared to their later-generation and native born counterparts, and to identify factors that may underlie these risks. Eighteen studies met full inclusion criteria. First generation immigrant adolescents experience higher rate of bullying and peer aggression compared to third generation and native counterparts. Refugee status and advanced parental age were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 57 publications
3
89
0
2
Order By: Relevance
“…33 The finding that, overall, immigration was not associated with assault-related firearm injuries is consistent with the finding of Chavez and colleagues, 34 who reported no association of neighbourhood-level immigration with changes in homicide rates. In our study, the observed variation in firearm injury by region of origin may have been related to higher participation in Canadian gangs by Indo-Asian, Caribbean and African immigrants than by those from other regions, and it highlights the need to ensure a healthy transition to Canada for these particular at-risk groups.…”
Section: Discussionsupporting
confidence: 87%
“…33 The finding that, overall, immigration was not associated with assault-related firearm injuries is consistent with the finding of Chavez and colleagues, 34 who reported no association of neighbourhood-level immigration with changes in homicide rates. In our study, the observed variation in firearm injury by region of origin may have been related to higher participation in Canadian gangs by Indo-Asian, Caribbean and African immigrants than by those from other regions, and it highlights the need to ensure a healthy transition to Canada for these particular at-risk groups.…”
Section: Discussionsupporting
confidence: 87%
“…[1][2][3][7][8][9] The AGREE is recognized internationally for evidence-based guideline development. 5 The steps we used are also in line with the checklist of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The family spent three years in a United Nations High Commissioner for Refugees refugee camp in Jordan and is now in Canada as part of a humanitarian resettlement program (Box 1). [1][2][3][4][5][6][7] Fatima is 28, Omar is 32, and Ruya (which means "vision" or "dream" in Arabic) is 4 years old. They have no health or immunization records with them.…”
mentioning
confidence: 99%
“…2 Access to safe and adequate housing, employment and income, family cohesion, and keeping parents and children together during and after the integration process may have strong protective health effects. 3,4 Conversely, difficult resettlement conditions, such as insecurity, economic difficulties, unemployment and social exclusion/isolation, can aggravate symptoms.…”
mentioning
confidence: 99%